The lay mirage of Ecuador. Constituent debates on abortion, homosexual adoption and the name of God in the preamble of the Constitution from a historical perspective - Espinoza Plua, Marjorie Gabriela (2018)
The Ecuadorian Constitution characterizes the State as a Lay State. However, during the Constituent Assembly of 2007 three topics challenged the idea of consecrating Ecuador as a Lay State: the right to life from conception, homosexual marriage and the inclusion of God in the preamble of the Constitution. This paper reconstructs the narrative of those debates and shows how religion shaped the conversation and impacted the provisions that were finally adopted. In light of this description, it is possible to observe that state secularism in Ecuador functions more as a mirage than as a catalyst to build a liberal democracy.